Learning Impact Role Playing Game Edukasi Terhadap Motivasi Belajar Sejarah Siswa: Learning Impact of Educational Role Playing Games on Students' History Learning Motivation - Wenda Novayani (Politeknik Caltex Riau, 2022)
This research is motivated by the lack of student motivation in learning history. Students find history lessons full of memorization and boring. Even though studying history has an important role in the life of a nation because history lessons instill values ​​of the spirit of patriotism, provide moral values, and build the character of a nation. Therefore, this study aims to see the historical Role Playing Game (RPG) 's learning impact on learning motivation and teaching the value of student attitudes from the material presented in the game. The method used in this research is a quantitative research method. The research subjects were 32 students of SMAN 9 Pekanbaru. Data was collected through a questionnaire with a reliability value of rxy = 0.884 and a validity value = 0.645 (> 0.349). The result showed that students' learning motivation significantly impacts their attitude and knowledge value. The RPG game of historical education gives effect to 88% knowledge improvement, attitude (patriotism, moral values ​​, and critical thinking) by 87% motivation, so that students are interested to learn and feel not bored with the average value of 89% with an excellent appraisal. Attitude values, and historical knowledge in the educational game, have a positive relationship with the motivation to learn. Learning history using historical RPG games provides a positive learning impact on student's motivation to learn history.